2023
DOI: 10.1002/ps.7361
|View full text |Cite
|
Sign up to set email alerts
|

Insecticide resistance management of Bemisia tabaci (Hemiptera: Aleyrodidae) in Australian cotton – pyriproxyfen, spirotetramat and buprofezin

Abstract: BACKGROUND: Bemisia tabaci is a globally significant agricultural pest including in Australia, where it exhibits resistance to numerous insecticides. With a recent label change, buprofezin (group 16), is now used for whitefly management in Australia. This study investigated resistance to pyriproxyfen (group 7C), spirotetramat (group 23) and buprofezin using bioassays and available molecular markers.RESULTS: Bioassay and selection testing of B. tabaci populations detected resistance to pyriproxyfen with resista… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 47 publications
0
4
0
Order By: Relevance
“…Similar levels of ketoenol resistance have been previously described in cotton whiteflies, B. tabaci , known as a notorious pest of greenhouse and field vegetables in Europe [ 31 , 35 ], which evolved resistance to almost all chemical classes of insecticides applied for its control [ 37 ]. Ketoenol resistance is not restricted to European B. tabaci populations but has recently also been demonstrated in Australian populations [ 32 , 34 ]. Another study reported a shift to lower ketoenol susceptibility in Greek and Spanish populations of greenhouse whiteflies, T. vaporariorum , but LC 50 -values for spiromesifen—despite some variation—remained well below the recommended label rates for spiromesifen [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar levels of ketoenol resistance have been previously described in cotton whiteflies, B. tabaci , known as a notorious pest of greenhouse and field vegetables in Europe [ 31 , 35 ], which evolved resistance to almost all chemical classes of insecticides applied for its control [ 37 ]. Ketoenol resistance is not restricted to European B. tabaci populations but has recently also been demonstrated in Australian populations [ 32 , 34 ]. Another study reported a shift to lower ketoenol susceptibility in Greek and Spanish populations of greenhouse whiteflies, T. vaporariorum , but LC 50 -values for spiromesifen—despite some variation—remained well below the recommended label rates for spiromesifen [ 36 ].…”
Section: Discussionmentioning
confidence: 99%
“…The strong impact of the A2083V mutation on ketoenol efficacy has been demonstrated and functionally validated in bioassays with transgenic Drosophila lines [ 32 ], and transgenic Caenorhabditis elegans [ 33 ]. Recent resistance monitoring campaigns utilizing molecular diagnostics revealed the presence of this mutation in Australian and Greek B. tabaci greenhouse and field populations, respectively [ 34 , 35 ]. Another target-site mutation, originally described in spiromesifen resistant T. vaporariorum , E645K [ 30 ], is located outside the CT domain, and its association with ketoenol resistance phenotypes was not confirmed [ 36 ].…”
Section: Introductionmentioning
confidence: 99%
“…They were split into two parts, reducing the R factor by about 5%. In particular, the site occupancy factor of the 2,5-dimethylphenyl group in the molecule containing N1 is 0.66(18): 0.34 (18), whereas the site occupancy factor of the 4-ethyl carbonate group in the molecule containing N2 is 0.6551(19): 0.3449 (19), and that of the 2,5-dimethylphenyl group is 0.624(11): 0.376 (11). Due to the limited availability of hydrogen bond donors, the crystal structure of form II also exhibits a relatively low abundance of hydrogen bonds.…”
Section: Spirotetramat Form IImentioning
confidence: 99%
“…Its mechanism of action involves inhibiting lipid biosynthesis, specifically by impeding the activity of acetyl-coenzyme A carboxylase during the lipid synthesis process in the targeted pests. Market research indicates that spirotetramat offers the advantages of comprehensive insecticidal properties with a broad spectrum , and a long-lasting effect . However, the disadvantages of low solubility and poor pesticide release rate and reports of spirotetramat resistance have persistently emerged in recent years. …”
Section: Introductionmentioning
confidence: 99%
“…In the management of invasive species, genomic resources are facilitating accurate and time-efficient diagnostics and surveillance (Chua et al, 2023; Frey et al, 2022; Gardy & Loman, 2018; Matheson & McGaughran, 2022; McGaughran et al, 2024), understanding the origin of invasive species, invasion pathways (Atsawawaranunt et al, 2023; Liu et al, 2022; Rane et al, 2023; Zhang et al, 2023), identifying genetic (Jin et al, 2023; Parvizi et al, 2023; Yin et al, 2021) and genome structural (Stapley et al, 2015; Tepolt et al, 2022) variation related to invasion potential (Camus et al, 2024; McGaughran et al, 2024; Sillero et al, 2020). These resources are also accelerating the ways in which invasive species are controlled, such as through chemical management (Hopkinson et al, 2023; Tay et al, 2022; Thia et al, 2023), biocontrol agents (Morrow & Riegler, 2021; Nikolouli et al, 2018; Ross et al, 2022), genome-informed population control (Burgess et al, 2022; Kennedy et al, 2018; Maselko et al, 2017), or gene-editing and gene drive (Devos et al, 2022; Hammond et al, 2016, 2021).…”
Section: Introductionmentioning
confidence: 99%